Collective Marketing Performance of Coffee Beans in Lampung Province - Irmayani Noer (AIBPM Publisher, 2022)
ThisÂ studyÂ aimsÂ toÂ identify actorsÂ in collective marketing channelsÂ and analyze the collective marketing performance of coffee beans in Lampung Province, Indonesia. Research samples are 50 coffee farmers in West Lampung Regency, randomly selected from farmer groups. The analytical method used to assess the collective marketing performance was marketing margin analysis.â€The results showed that many actors were involved in the marketing channel, including collectors, wholesalers, farmer groups, Federate Farmers Groups, Joint Business Groups, and exporters.â€Their involvement increased the handling costs during the marketing process. There are four collective marketing channels of coffee beans identified in this research.â€Based on the results of marketing margin analysis, it is known that the most efficient collective marketing channel is direct selling to Joint Business Group.â€